Impact of Membrane‐Induced Particle Immobilization on Seeded Growth Monitored by In Situ Liquid Scanning Transmission Electron Microscopy. Issue 20 (1st April 2016) - Weiner, Rebecca G.; Chen, Dennis P.; Unocic, Raymond R.; Skrabalak, Sara E.
Abstract : In situ liquid cell scanning transmission electron microscopy probes seeded growth in real time. The growth of Pd on Au nanocubes is monitored as a model system to compare growth within a liquid cell and traditional colloidal synthesis. Different growth patterns are observed due to seed immobilization and the highly reducing environment within the liquid cell.